Self–confined synthesis of HKUST‐1 membranes from CuO nanosheets at room temperature. Issue 1 (26th January 2016) - Guo, Yi; Mao, Yiyin; Hu, Pan; Ying, Yulong; Peng , Xinsheng
Abstract: Metal‐organic frameworks (MOFs) have drawn great interest in several applications. MOFs can be successfully synthesized by metal oxide or hydroxide, but the synthesis of MOFs membranes has been rarely reported. Here we found the CuO nanosheets (CuO NSs) were highly positively charged and reactive enough to form HKUST‐1 powders in trimesic acid (H3 BTC) ethanol‐water solution even at room temperature. Thus we design a self‐confined and healing strategy to prepared well‐intergrown HKUST‐1 membranes on macroporous support by solid‐to‐solid conversion from CuO NSs film. During the growth process, HKUST‐1 (Cu3 (BTC)2 ⋅3H2 O) crystals are self‐confined and tightly intergrown. The gaps and defects are healed with elongation growth time, resulting in a continuous and well‐intergrown HKUST‐1 membrane. The continuous and well intergrown HKUST‐1 thin membranes demonstrate good gas separation performance. The process presented here may pave a new way to prepare MOFs membranes by using active metal oxide nanostructures. Abstract : Positively charged CuO nanosheets are desirable for the growth of well–intergown HKUST‐1 membranes through a self–confined convertion process at room temperature and envieromental friedly. The HKUST‐1 membrane demonstrates nice gas separation performance.